Treatment of Posterior Cruciate Ligament Tibial Avulsion: A New Modified Open Direct Lateral Posterior Approach - Keyhani, Sohrab; Soleymanha, Mehran; Salari, Amir (The Journal of Knee Surgery, 2020)
The optimal operative technique for the treatment of the tibial-side avulsion injuries of the posterior cruciate ligament (PCL) is debatable. This study was aimed to evaluate the postoperative outcomes and complications if any after an open direct, posterolateral approach using cannulated cancellous screw fixation of a PCL tibial avulsion. From January 2016 to June 2018, 17 patients (14 males and 3 females) with PCL avulsion fraction treatment—who underwent open reduction and internal fixation using cannulated cancellous screws—were included in this prospective study. A direct posterolateral approach in the prone position was used in all cases. The Lysholm's knee score and International Knee Documentation Committee (IKDC) score were assessed preoperatively and during regular follow-up examinations for at least 1 year (12–20 months) postoperatively. All patients had fracture union and all of their knees were stable upon physical examination. No nerve or blood vessel injuries occurred. The mean Lysholm's scores and mean IKDC scores were improved significantly at the last follow-up. This study provides evidence that open direct posterolateral approach may be reliable for the treatment of tibial-sided bony PCL avulsion fractures. This approach can provide direct visualization of the posterior capsule and PCL avulsion site associated with good reduction and stable fixation, easy application of the screws directly from posterior to anteriorly without extensive soft tissue damage. Nevertheless, long-term follow-up is recommended.
Keywords: posterior cruciate ligament; avulsion fractures; direct posterolateral approach